A lithium-supplementing positive electrode material and its preparation method and application
By wrapping lithium-enhancing particles inside the positive electrode active material and covering a rigid coating to form a core-shell structure, the problem of positive electrode active lithium consumption during the first charging and discharging of lithium batteries is solved, and high energy density, excellent rate performance and cycle stability are achieved.
Patent Information
- Application Number
- CN202411624806.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-14
AI Technical Summary
During the first charging and discharging process of existing lithium batteries, the active lithium in the positive electrode is permanently consumed, resulting in a decrease in the Coulomb efficiency, capacity and energy density of the battery. The conductivity of the lithium supplement agent is insufficient, which easily leads to deterioration of the battery impedance and power performance.
By wrapping lithium-enhancing particles inside the positive electrode active material and covering the surface of the lithium-enhancing particles and the surface of the active material layer, a lithium-enhancing positive electrode material with a core-shell structure is formed to improve the structural strength and conductivity of the lithium-enhancing particles.
This method not only avoids the impact of the structural collapse of lithium supplement agent on battery stability, but also reduces the contact resistance between lithium supplement agent and active material, improves the conductivity of the positive electrode material, thereby improving the energy density, rate performance and cycle stability of the lithium battery.
Smart Images

Figure CN119170783B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a lithium-supplementing positive electrode material and a preparation method and application thereof. Background Art
[0002] During the first charge of a lithium-ion battery, the organic electrolyte will be reduced and decomposed on the surface of the negative electrode to form a solid electrolyte interface film, which will cause the active lithium in the positive electrode to be permanently consumed, thereby reducing the battery's coulombic efficiency, capacity and energy density. In order to increase the energy density of lithium batteries and reduce the consumption of lithium ions in the positive electrode material during the first charge and discharge process of lithium batteries, a high-capacity lithium supplement can be added to the positive electrode. This type of lithium supplement will release active lithium during the charging process to make up for the irreversible capacity loss during the first charge and discharge process.
[0003] However, the positive electrode lithium supplements currently used are one-time use, the lithium ions are irreversible, the structure is inactivated after charging is completed, it is easy to collapse and the conductivity is insufficient, which will deteriorate the battery's impedance, power and other performance.
[0004] Based on this, how to achieve lithium replenishment in the positive electrode while avoiding the introduction of lithium replenishers, structural collapse and other effects on the conductive properties of the positive electrode is one of the issues that urgently need to be considered in order to improve the comprehensive electrical performance of lithium batteries. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a lithium-supplementing positive electrode material and a preparation method and application thereof. By wrapping lithium-supplementing particles inside the positive electrode active material and coating the surface of the lithium-supplementing particles and the surface of the active material layer with a rigid coating, the structural strength of the lithium-supplementing particles is improved while the conductivity of the positive electrode material is improved. This can not only avoid the influence of the structural collapse of the lithium-supplementing particles after lithium replenishment on the stability of the battery, but also reduce the contact resistance between the lithium-supplementing agent and the active material and between the positive electrode materials, and enhance the conductivity of the positive electrode active material, so that the lithium-ion battery containing the lithium-supplementing positive electrode material has both high energy density and excellent rate performance and cycle stability.
[0006] Specifically, the following technical solutions are provided:
[0007] A first aspect of the present invention provides a lithium-supplementing positive electrode material having a core-shell structure, comprising a lithium-supplementing core, a first rigid coating, an active material layer and a second rigid coating arranged in sequence from the inside to the outside; wherein the first rigid coating and the second rigid coating both contain metal carbides and / or metal nitrides.
[0008] Further, the lithium-supplementing core contains a lithium-supplementing material, and the lithium-supplementing material is selected from one or more of lithium nickel oxide, lithium cobalt oxide, lithium high nickel oxide, and lithium-rich manganese-based materials; the active material layer contains a positive electrode active material, and the positive electrode active material is selected from one or more of lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, and lithium cobalt oxide; more preferably, the gram capacity of the lithium-supplementing material is greater than the gram capacity of the positive electrode active material.
[0009] Furthermore, the metal elements in the metal carbide and the metal nitride are selected from one or more of titanium, tungsten, zirconium, tantalum, chromium and vanadium.
[0010] Furthermore, the diameter of the lithium-supplemented core is 100-1000 nm, for example, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, etc., including but not limited to the diameter sizes listed above.
[0011] Further, the thickness of the first rigid coating is 10-100 nm, for example, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc., including but not limited to the thickness values listed above.
[0012] Furthermore, the thickness of the active material layer is 2-20 μm, for example, 2 μm, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, etc., including but not limited to the thickness values listed above.
[0013] Further, the thickness of the second rigid coating is 10-100 nm, for example, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc., including but not limited to the thickness values listed above.
[0014] Furthermore, the mass proportion of the lithium-supplemented core in the lithium-supplemented positive electrode material is 5%-20%, for example, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, etc., including but not limited to the mass proportions listed above.
[0015] The second aspect of the present invention provides a method for preparing the lithium-supplemented positive electrode material according to the first aspect, comprising the following steps:
[0016] S1, dispersing lithium-replenishing material particles in a first metal salt aqueous solution, performing a first vacuum stirring treatment, and then separating the solid and placing it in a first mixed atmosphere for a first calcination treatment to obtain a lithium-replenishing core material coated with a first rigid coating; the first mixed atmosphere comprises a protective atmosphere and an alkane gas;
[0017] S2, mixing the lithium-replenishing core material coated with the first rigid coating prepared in S1 with the positive electrode active material precursor salt, performing a second calcination treatment, coating the active material layer on the surface of the lithium-replenishing core material coated with the first rigid coating, and obtaining a lithium-replenishing positive electrode material precursor;
[0018] S3, dispersing the lithium-replenishing positive electrode material precursor prepared in S2 in a second metal salt aqueous solution, performing a second vacuum stirring treatment, then separating the solid and placing it in a second mixed atmosphere for a third calcination treatment, coating the surface of the lithium-replenishing positive electrode material precursor with a second rigid coating to obtain the lithium-replenishing positive electrode material; the second mixed atmosphere comprises a protective atmosphere and an alkane gas.
[0019] Furthermore, in step S1, the particle size of the lithium supplement material particles is 100-1000 nm, for example, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc.
[0020] Furthermore, in step S1, the first metal salt is selected from one or more of hydrochlorides, sulfates, and nitrates; and the metal element in the first metal salt is selected from one or more of titanium, tungsten, zirconium, tantalum, chromium, and vanadium.
[0021] Further, in step S1, the concentration of the first metal salt aqueous solution is 0.01-0.5 mol / L, for example, 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, etc., including but not limited to the concentration values listed above.
[0022] Furthermore, in the step S1, the time of the first vacuum stirring treatment is 2-4 hours.
[0023] Furthermore, in step S1, the protective atmosphere in the first mixed atmosphere is selected from one or more of nitrogen, argon, helium, and neon, and the alkane gas is selected from one or more of methane, ethane, and propane.
[0024] Furthermore, in the step S1, the temperature of the first calcination treatment is 800-1400°C and the time is 2-6 hours.
[0025] Furthermore, in step S2, when the positive electrode active material is lithium nickel cobalt manganese oxide, the lithium-supplementing core material coated with the first rigid coating is first dispersed in an aqueous solution containing nickel salt, cobalt salt and manganese salt, and vacuum stirred for 0.5-2 h, and then an alkaline solution is added and heated to react at 80-160 ° C, and the solid product is separated, and then the solid product is evenly mixed with the lithium salt, and a second calcination treatment is performed to obtain the lithium-supplementing positive electrode material precursor.
[0026] Furthermore, in the step S2, the temperature of the second calcination treatment is 800-1400°C and the time is 8-12 hours.
[0027] Furthermore, in step S3, the second metal salt is selected from one or more of hydrochlorides, sulfates, and nitrates; and the metal element in the second metal salt is selected from one or more of titanium, tungsten, zirconium, tantalum, chromium, and vanadium.
[0028] Further, in step S3, the concentration of the second metal salt aqueous solution is 0.01-0.5 mol / L, for example, 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, etc., including but not limited to the concentration values listed above.
[0029] Furthermore, in step S3, the second vacuum stirring treatment lasts for 2-4 hours.
[0030] Furthermore, in step S3, the protective atmosphere in the second mixed atmosphere is selected from one or more of nitrogen, argon, helium, and neon, and the alkane gas is selected from one or more of methane, ethane, and propane.
[0031] Furthermore, in the step S3, the temperature of the third calcination treatment is 800-1400°C and the time is 2-6h.
[0032] The third aspect of the present invention provides a positive electrode plate, comprising the lithium-supplementing positive electrode material described in the first aspect or the lithium-supplementing positive electrode material prepared by the preparation method described in the second aspect.
[0033] Furthermore, the positive electrode plate comprises a current collector and a positive electrode active layer arranged on at least one side of the current collector along the thickness direction, and the positive electrode active layer is composed of the lithium-supplementing positive electrode material and a binder.
[0034] Furthermore, the mass proportion of the lithium-supplementing positive electrode material in the positive electrode active layer is 95%-98%.
[0035] A fourth aspect of the present invention provides a lithium-ion battery comprising the positive electrode sheet described in the third aspect.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] The present invention provides a lithium-supplementing positive electrode material with a core-shell structure, wherein lithium-supplementing particles are wrapped inside a positive electrode active material, and a conductive rigid coating is coated on the surface of the lithium-supplementing particles and the surface of the active material layer. The formed lithium-supplementing positive electrode material has a low specific surface area, a high compaction density and a high electrical conductivity.
[0038] Compared with the traditional lithium replenishment method of adding a lithium replenisher to the positive electrode slurry, the lithium replenishing positive electrode material provided by the present invention has a good lithium replenishing effect without the need to add a lithium replenisher, and can effectively avoid direct external contact between the lithium replenisher and the active material. In addition, the rigid coating provided between the lithium replenishing core and the active material layer of the present invention can not only improve the structural strength of the lithium replenishing core, but also reduce the contact resistance between the lithium replenishing core and the active material layer. Therefore, the above-mentioned lithium replenishing positive electrode material is used to construct a lithium battery, which can effectively avoid the deterioration of the contact impedance between the active material and the lithium replenishing agent due to the introduction of the lithium replenisher and the collapse of the lithium replenisher structure after lithium replenishment, which is beneficial to improve the conductivity of the lithium replenishing positive electrode and reduce the battery impedance.
[0039] In addition, the lithium-supplementing positive electrode material provided by the present invention has high conductivity and good lithium-supplementing effect. When preparing the positive electrode active slurry, the conductive agent and lithium-supplementing agent components in the positive electrode formula can be reduced or eliminated, which can not only simplify the formula of the positive electrode active slurry, facilitate homogenization, and improve production efficiency; but also increase the proportion of active materials in the positive electrode active slurry, thereby improving the overall energy density of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 A schematic diagram of the structure of the lithium-supplementing positive electrode material prepared in Example 1;
[0041] Icon: 1 is the lithium-supplemented core, 2 is the first rigid coating, 3 is the active material layer, and 4 is the second rigid coating. DETAILED DESCRIPTION
[0042] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are for the purpose of describing specific embodiments only and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items. The "include" or "comprising" described in the present invention means that in addition to the components described, other components may also be included or contained. The "include" or "comprising" described in the present invention may also be replaced by the closed "for" or "consisting of...".
[0043] As described in the background technology, currently, a high-capacity lithium supplement is usually added to the positive electrode to supplement the irreversible capacity loss during the first charge and discharge process of the lithium battery. However, due to its one-time use characteristics, the positive electrode lithium supplement is irreversible, and the structure is inactivated after charging, and it is easy to collapse and the conductivity is insufficient, which will deteriorate the impedance, power and other performance of the battery. Therefore, how to achieve positive electrode lithium supplement while avoiding the introduction of lithium supplements, structural collapse and other effects on the conductivity of the positive electrode is one of the problems that need to be solved urgently to improve the comprehensive electrical performance of lithium batteries.
[0044] To solve the above problems, an embodiment of the present invention provides a lithium-supplementing positive electrode material, which has a core-shell structure, including a lithium-supplementing core, a first rigid coating, an active material layer and a second rigid coating arranged in sequence from the inside to the outside; wherein the first rigid coating and the second rigid coating both contain metal carbides and / or metal nitrides.
[0045] The present invention provides a lithium-replenishing positive electrode material to achieve positive electrode lithium replenishment while avoiding the introduction of lithium replenishing agents and the influence of structural collapse after lithium replenishment on battery performance. The lithium-replenishing positive electrode material is obtained by wrapping lithium-replenishing particles inside the positive electrode active material and coating the surface of the lithium-replenishing particles and the surface of the active material layer with a rigid coating. The lithium-replenishing positive electrode material has a low specific surface area, a high compaction density and a high electrical conductivity. Specifically: the above-mentioned lithium-replenishing positive electrode material with a core-shell structure wraps the lithium-replenishing particles inside the positive electrode active material, and the first rigid coating disposed between the lithium-replenishing core and the active material layer can improve the structural strength of the lithium-replenishing core, and the rigid coating composed of metal carbides and / or metal nitrides has high conductivity, which can reduce the contact impedance between the lithium-replenishing core and the active material layer; at the same time, the second rigid coating disposed on the outer surface of the active material layer can reduce the contact between the positive electrode active material and the electrolyte, inhibit the occurrence of interface side reactions, and the second rigid coating can further improve the conductivity and structural stability of the lithium-replenishing positive electrode material, thereby improving the energy density and cycle life of the battery. The lithium-replenishing positive electrode material provided by the present invention is used to construct a lithium battery. When preparing the positive electrode lithium-replenishing active slurry, there is no need to add additional lithium-replenishing agents and conductive agents, which not only simplifies the formula of the positive electrode lithium-replenishing active slurry and facilitates homogenization, but also increases the proportion of positive electrode materials in the positive electrode active slurry, further improving the overall energy density of the battery; more importantly, the use of the lithium-replenishing positive electrode material can achieve a good lithium-replenishing effect while effectively avoiding the introduction of the lithium-replenishing agent and the collapse of the lithium-replenishing agent structure after lithium replenishment, which deteriorates the conductivity of the positive electrode.
[0046] In the present invention, the lithium-supplementing core contains lithium-supplementing materials, and the active material layer contains positive electrode active materials, wherein the gram capacity of the lithium-supplementing material is greater than the gram capacity of the positive electrode active material; preferably, the lithium-supplementing material can be selected from one or more of lithium nickel oxide, lithium cobalt oxide, lithium high nickel oxide, and lithium-rich manganese-based materials, and the positive electrode active material can be selected from one or more of lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium iron manganese phosphate, and lithium cobalt oxide.
[0047] In the present invention, the metal elements in the metal carbide and the metal nitride are selected from one or more of titanium, tungsten, zirconium, tantalum, chromium, and vanadium. Such metal carbides and metal nitrides have excellent rigidity and electrical conductivity. In some preferred embodiments, the first rigid coating and the second rigid coating are made of titanium carbide, tungsten carbide, zirconium carbide, tungsten nitride, etc.
[0048] In the present invention, the diameter of the lithium-supplemented core is preferably 100-1000 nm, for example, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, etc., including but not limited to the diameters listed above.
[0049] In the present invention, the thickness of the first rigid coating is preferably 10-100 nm, for example, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc., including but not limited to the thickness values listed above.
[0050] In the present invention, the thickness of the active material layer is preferably 2-20 μm, for example, 2 μm, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, etc., including but not limited to the thickness values listed above.
[0051] In the present invention, the thickness of the second rigid coating is 10-100 nm, for example, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc., including but not limited to the thickness values listed above.
[0052] In the present invention, the mass proportion of the lithium-supplemented core in the lithium-supplemented positive electrode material is 5%-20%, for example, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, etc., including but not limited to the mass proportions listed above.
[0053] The present invention also provides a method for preparing the above-mentioned lithium-supplemented positive electrode material, comprising the following steps:
[0054] S1, dispersing lithium-replenishing material particles in a first metal salt aqueous solution, performing a first vacuum stirring treatment, and then separating the solid and placing it in a first mixed atmosphere for a first calcination treatment to obtain a lithium-replenishing core material coated with a first rigid coating; the first mixed atmosphere comprises a protective atmosphere and an alkane gas;
[0055] S2, mixing the lithium-replenishing core material coated with the first rigid coating prepared in S1 with the positive electrode active material precursor salt, performing a second calcination treatment, coating the active material layer on the surface of the lithium-replenishing core material coated with the first rigid coating, and obtaining a lithium-replenishing positive electrode material precursor;
[0056] S3, dispersing the lithium-replenishing positive electrode material precursor prepared in S2 in a second metal salt aqueous solution, performing a second vacuum stirring treatment, then separating the solid and placing it in a second mixed atmosphere for a third calcination treatment, coating the surface of the lithium-replenishing positive electrode material precursor with a second rigid coating to obtain the lithium-replenishing positive electrode material; the second mixed atmosphere comprises a protective atmosphere and an alkane gas.
[0057] The present invention also provides a method for preparing the above-mentioned lithium-replenishing positive electrode material, by in-situ synthesizing metal carbides (such as titanium carbide, zirconium carbide, etc.) on the surface of lithium-replenishing material particles, thereby forming a first rigid coating tightly bonded to the surface of the lithium-replenishing material particles, and then mixing the lithium-replenishing core material coated with the first rigid coating with a positive electrode active material precursor salt, and after calcination, forming a tightly bonded active material layer on the surface of the first rigid coating, and finally synthesizing metal carbides in-situ on the active material layer to form a second rigid coating. The lithium-replenishing positive electrode material prepared by the above-mentioned preparation method has tight bonding between the layers, and has better structural stability and electrical conductivity.
[0058] In some preferred embodiments, in step S1, the particle size of the lithium supplement material particles is 100-1000 nm, for example, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc.
[0059] In some preferred embodiments, in step S1, the first metal salt is selected from one or more of hydrochlorides, sulfates, and nitrates; the metal element in the first metal salt is selected from one or more of titanium, tungsten, zirconium, tantalum, chromium, and vanadium; the concentration of the first metal salt aqueous solution is preferably 0.01-0.5 mol / L, for example, 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, etc., including but not limited to the concentration values listed above.
[0060] In some preferred embodiments, in step S1, the time of the first vacuum stirring treatment is 2-4 h, such as 2 h, 3 h, 4 h, etc.
[0061] In some preferred embodiments, in step S1, the first calcination treatment is carried out under a first mixed atmosphere, wherein the first mixed atmosphere contains a protective atmosphere and an alkane gas, so that the first metal salt on the surface of the lithium supplement material particles reacts with the small molecule gas carbon source to form a metal carbide; preferably, the protective atmosphere contained in the first mixed atmosphere can be selected from one or more of nitrogen, argon, helium, and neon, and the alkane gas can be selected from one or more of methane, ethane, and propane.
[0062] In some preferred embodiments, in step S1, the temperature of the first calcination treatment is preferably 800-1400°C, for example, 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, etc., and the time of the first calcination treatment is preferably 2-6 h, for example, 2 h, 3 h, 4 h, 5 h, 6 h, etc.
[0063] In some preferred embodiments, in step S2, when the positive electrode active material is lithium nickel cobalt manganese oxide, the lithium-supplementing core material coated with the first rigid coating is first dispersed in an aqueous solution containing nickel salt, cobalt salt and manganese salt, and vacuum stirred for 0.5-2 h, and then an alkaline solution is added and heated to react at 80-160 ° C, and the solid product is separated, and then the solid product is evenly mixed with the lithium salt, and a second calcination treatment is performed to obtain the above-mentioned lithium-supplementing positive electrode material precursor.
[0064] In some preferred embodiments, in step S2, the temperature of the second calcination treatment is preferably 800-1400°C, for example, 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, etc., and the time of the second calcination treatment is preferably 2-6 h, for example, 2 h, 3 h, 4 h, 5 h, 6 h, etc.
[0065] In some preferred embodiments, in step S3, the second metal salt can be selected from one or more of hydrochlorides, sulfates, and nitrates, the metal element in the second metal salt can be selected from one or more of titanium, tungsten, zirconium, tantalum, chromium, and vanadium, and the concentration of the second metal salt aqueous solution is 0.01-0.5 mol / L, for example, 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, etc., including but not limited to the concentration values listed above.
[0066] In some preferred embodiments, in step S3, the time of the second vacuum stirring treatment is 2-4 h, such as 2 h, 3 h, 4 h, etc.
[0067] In some preferred embodiments, in step S3, the protective atmosphere in the second mixed atmosphere is selected from one or more of nitrogen, argon, helium, and neon, and the alkane gas is selected from one or more of methane, ethane, and propane, wherein the alkane gas reacts with the second metal salt on the surface of the active material layer to form a corresponding metal carbide.
[0068] In some preferred embodiments, in step S3, the temperature of the third calcination treatment is preferably 800-1400°C, for example, 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, etc., and the time of the third calcination treatment is preferably 2-6 h, for example, 2 h, 3 h, 4 h, 5 h, 6 h, etc.
[0069] In the preparation method provided by the present invention, the temperatures of the first, second and third calcination treatments will affect the structural stability of the rigid coating, the lithium-supplementing material and the positive electrode active material. If the calcination temperature is too low, the C-metal bond energy in the rigid coating formed is low and the structural stability is poor. If the calcination temperature is too high, it will cause structural losses of the lithium-supplementing material, the positive electrode active material, etc., resulting in a decrease in electrochemical performance. Therefore, in order to obtain a lithium-supplementing positive electrode material with good structural stability and excellent electrochemical performance, the temperatures of the first, second and third calcination treatments need to be controlled in a suitable range, for example, within the range of 800-1400°C, to improve the battery energy density and cycle life.
[0070] In addition, the embodiments of the present invention also provide a positive electrode plate, which includes the above-mentioned lithium-supplementing positive electrode material.
[0071] In some preferred embodiments, the positive electrode plate includes a current collector and a positive electrode active layer arranged on at least one side of the current collector along the thickness direction. The positive electrode active layer is composed of the above-mentioned lithium-replenishing positive electrode material and a binder, and does not require the addition of additional lithium-replenishing agents and conductive agents. It can have good lithium-replenishing effect and conductivity; preferably, the mass proportion of the lithium-replenishing positive electrode material in the positive electrode active layer is 95%-98%.
[0072] The present invention also provides a lithium-ion battery comprising the above-mentioned positive electrode plate, which has high energy density while exhibiting low internal resistance, high rate performance and excellent cycle stability.
[0073] The present invention is further described below in conjunction with specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention. Example 1
[0074] This embodiment relates to the preparation of a lithium-supplemented positive electrode material and a positive electrode sheet, which is specifically as follows:
[0075] Preparation of lithium-supplemented positive electrode materials:
[0076] (1) The commercially available lithium-replenishing material lithium nickelate was ground in a ball mill for 2 h until its particle size was 500 nm, and then evenly dispersed in a 0.1 mol / L titanium tetrachloride solution and stirred in a vacuum for 2 h. The solid was separated and transferred to a muffle furnace. Methane gas was introduced under nitrogen protection and reacted at 1200 °C for 4 h to obtain a lithium-replenishing core material coated with a first rigid coating (titanium carbide with a thickness of about 40 nm).
[0077] (2) The lithium-replenishing core material coated with the first rigid coating prepared in step (1) is ground into a particle size of about 500 nm by a ball mill for later use; nickel salt, cobalt salt and manganese salt are dissolved in water to obtain a precursor salt solution; the ground lithium-replenishing core material coated with the first rigid coating is dispersed in the precursor salt solution, vacuum stirred for 1 h, and then an ammonia solution is added to the mixed solution until the pH of the solution is about 12, and the mixture is reacted at 140°C for 18 h, and then the precipitated product is filtered and dried, and then mixed with lithium carbonate in a mass ratio of 90%:10%, and calcined at 1200°C for 10 h to obtain a lithium-replenishing positive electrode material precursor with a particle size of about 10 μm.
[0078] (3) The lithium-replenishing cathode material precursor prepared in step (2) is uniformly dispersed in a 0.1 mol / L titanium tetrachloride solution, stirred in vacuum for 2 h, the solid is separated, and transferred to a muffle furnace. Methane gas is introduced under nitrogen protection conditions, and the reaction is carried out at 1200 °C for 4 h to obtain a lithium-replenishing cathode material coated with a second rigid coating (titanium carbide with a thickness of about 40 nm), wherein the lithium-replenishing cathode material accounts for about 15% by mass in the lithium-replenishing cathode material.
[0079] Preparation of positive electrode:
[0080] The positive electrode sheet was prepared using the lithium-supplemented positive electrode material prepared in this embodiment as the positive electrode active material. The positive electrode active material and the binder (PVDF5130) were mixed at a mass ratio of 98:2, and NMP was added and stirred to form a uniformly mixed and stable positive electrode slurry. The positive electrode slurry was evenly coated on the positive electrode current collector (aluminum foil with a thickness of 13 μm) with a coating surface density of 195 g / m 2 After drying and cold pressing, the compacted density is 3.4 g / cm 3 The positive electrode. Example 2
[0081] This embodiment relates to the preparation of a lithium-supplementing positive electrode material and a positive electrode sheet. The difference from Embodiment 1 is that the thickness of the first and second rigid coatings is about 60 nm, and the rest are the same, thereby obtaining a corresponding lithium-supplementing positive electrode material and a positive electrode sheet. Example 3
[0082] This embodiment relates to the preparation of a lithium-supplementing positive electrode material and a positive electrode sheet, which is different from Embodiment 1 in that the particle size of the lithium-supplementing material particles is controlled at about 800 nm, and the rest are the same, thereby obtaining a corresponding lithium-supplementing positive electrode material and a positive electrode sheet. Example 4
[0083] This embodiment relates to the preparation of a lithium-supplementing positive electrode material and a positive electrode sheet, which is different from Embodiment 1 in that the particle size of the lithium-supplementing material particles is controlled at about 1000 nm, and the rest are the same, thereby obtaining a corresponding lithium-supplementing positive electrode material and a positive electrode sheet. Example 5
[0084] This embodiment relates to the preparation of a lithium-supplementing positive electrode material and a positive electrode sheet. The difference from Embodiment 1 is that the reaction temperature in steps (1) and (3) is 800° C., and the rest are the same, to obtain the corresponding lithium-supplementing positive electrode material. Example 6
[0085] This embodiment relates to the preparation of a lithium-supplementing positive electrode material and a positive electrode sheet. The difference from Embodiment 1 is that the reaction temperature in steps (1) and (3) is 1400° C., and the rest are the same, to obtain the corresponding lithium-supplementing positive electrode material. Comparative Example 1
[0086] This comparative example relates to the preparation of a lithium-supplementing positive electrode material and a positive electrode sheet, which is different from Example 1 in that the particle size of the lithium-supplementing material particles is controlled at about 2000 nm, and the rest are the same, thereby obtaining a corresponding lithium-supplementing positive electrode material and a positive electrode sheet. Comparative Example 2
[0087] This comparative example involves the preparation of a lithium-replenishing positive electrode material and a positive electrode plate, which is different from Example 1 in that the first rigid coating is not coated on the surface of the lithium-replenishing material particles, and the rest is the same, thereby obtaining a corresponding lithium-replenishing positive electrode material and a positive electrode plate. Comparative Example 3
[0088] This comparative example relates to the preparation of a lithium-supplementing positive electrode material and a positive electrode sheet, which is different from Example 1 in that the reaction temperature in steps (1) and (3) is 600° C., and the rest are the same, to obtain the corresponding lithium-supplementing positive electrode material. Comparative Example 4
[0089] This comparative example involves the preparation of a lithium-replenishing positive electrode material and a positive electrode sheet. The only difference from Example 1 is that the positions of the lithium-replenishing material and the active material are replaced, and the mass proportion of the lithium-replenishing material in the lithium-replenishing positive electrode material is controlled to be about 15%. The other operations are the same. A lithium-replenishing positive electrode material with an active material as the core and sequentially coated with a first rigid coating, a lithium-replenishing layer and a second rigid coating, and a corresponding positive electrode sheet are prepared. Comparative Example 5
[0090] This comparative example involves the preparation of a positive electrode material and a positive electrode sheet, and the specific operations are as follows:
[0091] Preparation of positive electrode materials: nickel salt, cobalt salt and manganese salt are dissolved in water to obtain a precursor salt solution, ammonia solution is added to the precursor salt solution until the pH of the solution is about 12, and the reaction is carried out at 140 °C for 18 h. The precipitated product is then filtered and dried, and the product is evenly mixed with lithium carbonate according to the stoichiometric ratio of the metal elements in lithium nickel cobalt manganese oxide, and calcined at 1200 °C for 10 h to obtain lithium nickel cobalt manganese oxide.
[0092] The prepared nickel cobalt manganese oxide was used as the positive electrode active material, commercially available nickel oxide was used as the lithium supplement (particle size was about 500 nm), and the conductive carbon black and binder (PVDF5130) were mixed in a mass ratio of 81.6:14.4:2:2. NMP was added and stirred to form a uniform and stable positive electrode slurry. The positive electrode slurry was evenly coated on the positive electrode current collector (13 μm thick aluminum foil) with a coating surface density of 195 g / m 2 After drying and cold pressing, the compacted density is 3.4 g / cm 3 The positive electrode.
[0093] Application and performance testing
[0094] (1) The physical and chemical properties of the lithium-supplemented positive electrode materials or positive electrode materials prepared in the above embodiments and comparative examples were tested, and the test results are as follows:
[0095] Specific surface area test: Take samples of the same mass and measure them using the N2 adsorption method. The amount of gas adsorbed is used to characterize the specific surface area of the material.
[0096] Maximum compaction density: squeeze a certain amount of powder m into a block under different pressures, record the block volume V corresponding to the powder particles starting to break, and calculate the maximum compaction density, which is m / V; observe the particle surface and cross-section state through SEM to determine whether the powder is broken;
[0097] Conductivity test: Take the same mass of positive electrode material and squeeze it into blocks of the same thickness, then place it on a four-probe resistivity tester to test the conductive properties of the material.
[0098] The above test results are shown in Table 1 below:
[0099] Table 1
[0100]
[0101] It can be seen from Table 1 that compared with a single nickel cobalt manganese oxide lithium positive electrode material (Comparative Example 5), the lithium-supplemented positive electrode materials with a specific core-shell structure prepared in Examples 1 to 6 have low specific surface area, high compaction density and high conductivity. This is because the presence of the rigid coating can reduce the specific surface area of the positive electrode material, reduce the contact area between the positive electrode material and the electrolyte, and the rigid coating can further isolate the contact between the positive electrode material and the electrolyte, thereby reducing the occurrence of side reactions, which is beneficial to improving the cycle performance; in addition, the presence of the rigid coating greatly increases the compaction density of the positive electrode material, which is beneficial to the improvement of energy density, and the rigid coating with good conductivity reduces the contact impedance between the positive electrode materials, which is beneficial to reducing the internal resistance of the battery and improving the battery rate performance.
[0102] In addition, it can be seen from Examples 1 and 2 that as the thickness of the rigid coating increases, the specific surface area of the lithium-supplemented positive electrode material decreases, and the compaction density and conductivity increase, which further illustrates that the presence of the rigid coating can improve the structural strength and conductivity of the positive electrode material. It can also be seen from Examples 1, 3, 4 and Comparative Example 1 that if the particle size of the lithium-supplemented core is too large, the compaction density and conductivity will be reduced.
[0103] It can be seen from Example 1 and Comparative Example 2 that the provision of the first rigid coating between the lithium supplement core and the active material layer can effectively improve the overall compaction density and electrical conductivity, which is beneficial to the improvement of the battery energy density and rate performance.
[0104] It can be seen from Examples 1, 5, 6 and Comparative Example 3 that the sintering temperature of the rigid coating will affect the maximum compaction density and conductivity of the lithium-supplementing positive electrode material. Within a certain range, such as 600-1400°C, the compaction density and conductivity of the lithium-supplementing positive electrode material increase with the increase of the sintering temperature. It can be seen from Example 1 and Comparative Example 4 that by exchanging the positions of the active material and the lithium-supplementing material, that is, using the active material as the core layer, the compaction density and conductivity of the prepared lithium-supplementing positive electrode material are greatly reduced, which also shows that the replacement of the active material and the lithium-supplementing material will reduce the structural stability and conductivity of the lithium-supplementing positive electrode material.
[0105] (2) The positive electrode sheets prepared in the above-mentioned embodiments and comparative examples are respectively used to construct lithium-ion batteries, as follows:
[0106] Positive electrode sheet: the positive electrode sheet prepared in the above-mentioned embodiment and comparative example;
[0107] Negative electrode sheet: Mix the negative electrode active material (graphite and silicon oxide material mixed in a mass ratio of 8:2) with the conductive agent (conductive carbon black), PAA, and SBR in a ratio of 95.5:1.5:2:1, add deionized water and stir to form a uniform and stable negative electrode slurry. Evenly coat the negative electrode slurry on the negative electrode current collector (6 μm thick copper foil) with a coating surface density of 105 g / m 2 After drying and cold pressing, the compacted density is 1.5 g / cm 3 The negative electrode;
[0108] Diaphragm: The diaphragm uses a conventional PP / PE+PCS+glue layer diaphragm, and the model used here is a 7+3+3+3 μm lithium ion diaphragm;
[0109] Electrolyte: LiPF6 was dissolved in a solvent of ethylene carbonate, ethyl methyl carbonate, and diethyl carbonate in a volume ratio of 1:1:1 to obtain an electrolyte with a concentration of 1.2 mol / L;
[0110] Battery assembly: Arrange the positive electrode sheet, separator, negative electrode sheet, and separator in order, and wind them into a battery cell. Inject the electrolyte into the dry battery cell. After soaking for 24 hours, form it at 45 °C. The formation process is: charge at 0.05C to 3.4 V, and then charge at 0.2 C to 3.75 V. After aging at room temperature for 24 hours, the battery production is completed.
[0111] The electrochemical performance of the lithium-ion batteries constructed with different positive electrode sheets was tested. The specific test process is as follows:
[0112] Internal resistance test: First, charge the battery to 4.25 V at a constant current of 0.5 C, and then charge it to 0.05 C at a constant voltage of 4.25 V; let it stand for 30 min; then discharge it at a constant current of 0.5 C for 1 h, which is 50% SOC; after standing for 60 min, use a multimeter to clamp the positive and negative poles of the battery and test the internal resistance of the battery at 1 kHz. The multimeter reading is the AC internal resistance value of the battery.
[0113] Energy density test: The battery was placed in a 25°C environment for 30 min, charged at a constant current of 0.5 C to 4.25 V, charged at a constant voltage to 0.05 C, placed in a 30 min environment, and discharged at 1 C to 2.5 V. The discharge capacity and discharge voltage data of the test were collected. At this time, energy density = discharge capacity × average voltage / battery weight.
[0114] Rate performance test: 1. Charge at 0.5 C constant current to 4.25 V, then charge at 4.25 V constant voltage to 0.05 C; 2. Stand for 30 min; 3. Discharge at 0.5 C current to the lower limit voltage of 2.5 V, record the 0.5 C discharge capacity; 4. Stand for 30 min; then repeat steps 1-4 in sequence, discharge at 5 C current, and record the 5 C discharge capacity. 5 C rate retention rate = 5 C discharge capacity / 0.5 C discharge capacity.
[0115] Cycle performance test: Perform charge and discharge tests according to the standard test process 0.5 C / 1 C system until the discharge capacity of the battery is lower than 80% of the initial capacity. Stop the test and record the capacity retention rate after 500 cycles. The specific process is as follows: 1. The battery is left at 25 °C for 30 minutes, charged to 4.25 V at 0.5 C constant current, charged to 0.05 C at constant voltage, left at 30 minutes, and discharged to 2.5 V at 1 C. The discharge capacity of the first cycle is recorded as the initial capacity. If the capacity retention rate of 500 cycles = the discharge capacity of the 500th cycle / the discharge capacity of the first cycle.
[0116] The above test results are shown in Table 2 below:
[0117] Table 2
[0118]
[0119] It can be seen from Table 2 that compared with the lithium-ion battery constructed by the positive electrode sheet prepared by the traditional positive electrode lithium replenishment method in Comparative Example 5, the lithium-ion battery constructed by the positive electrode sheet prepared by Examples 1-6 has a low internal resistance, a higher energy density, and better rate performance and cycle stability.
[0120] It can be seen from Examples 1, 3, 4 and Comparative Example 1 that if the particle size of the lithium-supplemented core is too large, the internal resistance of the battery will increase, the battery energy density will decrease, and the battery rate performance and cycle stability will also decrease significantly. This is because the particle size of the lithium-supplemented core is too large, which will reduce the conductivity of the lithium-supplemented positive electrode material, and the structure will be inactivated after lithium replenishment, which will make it easier to reduce the overall structural strength of the positive electrode material, thereby having a greater impact on the battery rate performance and cycle stability.
[0121] It can be seen from Examples 1, 2 and Comparative Example 2 that the presence of the first and second rigid coatings in the lithium-supplementing positive electrode material can significantly reduce the internal resistance of the battery and improve the energy density, rate performance and cycle stability of the battery. This is because the presence of the rigid coating can greatly improve the structural stability and electrical conductivity of the lithium-supplementing positive electrode material, wherein the first rigid coating can effectively reduce the interface resistance between the lithium-supplementing material and the positive electrode active material, while reducing the effect of the structural deactivation of the lithium-supplementing material after lithium replenishment on the conductivity of the positive electrode, thereby effectively improving the rate performance and cycle stability of the lithium battery.
[0122] It can be seen from Examples 1, 5, 6 and Comparative Example 3 that the sintering temperature of the rigid coating as described above will affect the structural stability and electrical conductivity of the rigid coating. When the sintering temperature is too low, for example, the lithium-ion battery constructed with the lithium-supplemented positive electrode material prepared in Comparative Example 3 has an increased internal resistance, and its rate performance and cycle stability are reduced compared to Example 1.
[0123] In addition, it can be seen from Example 1 and Comparative Example 4 that if the active material and the lithium-replenishing material in Example 1 are swapped to prepare a lithium-replenishing positive electrode material (Comparative Example 4) with the active material as the core layer and sequentially coated with a first rigid coating, a lithium-replenishing layer and a second rigid coating, the structural stability and conductivity are significantly reduced, so that the lithium-ion battery constructed therefrom not only has a high internal resistance, but also has poor rate performance and cycle stability.
[0124] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.
Claims
1. A lithium-supplementing positive electrode material, characterized in that: The lithium-supplementing positive electrode material has a core-shell structure, including a lithium-supplementing core, a first rigid coating, an active material layer and a second rigid coating arranged in sequence from the inside to the outside; Wherein, the first rigid coating and the second rigid coating both contain metal carbides and / or metal nitrides; the metal elements in the metal carbides and metal nitrides are selected from one or more of titanium, tungsten, zirconium, tantalum, chromium, and vanadium; The diameter of the lithium-supplementing core is 100-1000 nm.
2. The lithium-supplementing positive electrode material according to claim 1, characterized in that: The lithium-supplementing core comprises a lithium-supplementing material, and the lithium-supplementing material is selected from one or more of lithium nickelate, lithium cobaltate, lithium pernickelate, and lithium-rich manganese-based materials; The active material layer comprises a positive electrode active material, and the positive electrode active material is selected from one or more of lithium nickel cobalt manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, and lithium cobalt oxide; The gram capacity of the lithium supplement material is greater than the gram capacity of the positive electrode active material.
3. The lithium-supplementing positive electrode material according to claim 1, characterized in that: Contain at least one of the following characteristics: (1) The thickness of the first rigid coating is 10-100 nm; (2) The thickness of the active material layer is 2-20 μm; (3) The thickness of the second rigid coating is 10-100 nm; (4) The mass proportion of the lithium-supplementing core in the lithium-supplementing positive electrode material is 15%-20%.
4. A method for preparing the lithium-supplemented positive electrode material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, dispersing lithium supplement material particles in a first metal salt aqueous solution, performing a first vacuum stirring treatment, and then separating the solid and placing it in a first mixed atmosphere for a first calcination treatment to obtain a lithium supplement core material coated with a first rigid coating; the first mixed atmosphere includes a protective atmosphere and an alkane gas; the temperature of the first calcination treatment is 1200-1400° C.; S2, mixing the lithium-replenishing core material coated with the first rigid coating prepared in S1 with the positive electrode active material precursor salt, performing a second calcination treatment, coating the active material layer on the surface of the lithium-replenishing core material coated with the first rigid coating, and obtaining a lithium-replenishing positive electrode material precursor; S3. Disperse the lithium-replenishing positive electrode material precursor prepared in S2 in a second metal salt aqueous solution, perform a second vacuum stirring treatment, then separate the solid and place it in a second mixed atmosphere for a third calcination treatment, and coat the surface of the lithium-replenishing positive electrode material precursor with a second rigid coating to obtain the lithium-replenishing positive electrode material; the second mixed atmosphere contains a protective atmosphere and an alkane gas; the temperature of the third calcination treatment is 1200-1400°C.
5. The preparation method according to claim 4, characterized in that: The step S1 includes at least one of the following features: (1) The particle size of the lithium supplement material particles is 100-1000 nm; (2) the first metal salt is selected from one or more of hydrochlorides, sulfates, and nitrates; the metal element in the first metal salt is selected from one or more of titanium, tungsten, zirconium, tantalum, chromium, and vanadium; (3) The concentration of the first metal salt aqueous solution is 0.01-0.5 mol / L; (4) The first vacuum stirring treatment lasts for 2-4 hours; (5) the protective atmosphere in the first mixed atmosphere is selected from one or more of nitrogen, argon, helium, and neon, and the alkane gas is selected from one or more of methane, ethane, and propane; (6) The time of the first calcination treatment is 2-6 hours.
6. The preparation method according to claim 4, characterized in that: In the step S2, When the positive electrode active material is lithium nickel cobalt manganese oxide, the lithium supplement core material coated with the first rigid coating is first dispersed in an aqueous solution containing nickel salt, cobalt salt and manganese salt, and then stirred in vacuum for 0.5-2h, and then an alkaline solution is added and heated at 80-160°C for reaction, and a solid product is separated, and then the solid product is evenly mixed with a lithium salt, and a second calcination treatment is performed to obtain the lithium supplement positive electrode material precursor; The temperature of the second calcination treatment is 800-1400° C. and the time is 8-12 hours.
7. The preparation method according to claim 4, characterized in that: The step S3 includes at least one of the following features: (1) The second metal salt is selected from one or more of hydrochlorides, sulfates, and nitrates; the metal element in the second metal salt is selected from one or more of titanium, tungsten, zirconium, tantalum, chromium, and vanadium; (2) the concentration of the second metal salt aqueous solution is 0.01-0.5 mol / L; (3) The second vacuum stirring treatment lasts for 2-4 hours; (4) the protective atmosphere in the second mixed atmosphere is selected from one or more of nitrogen, argon, helium, and neon, and the alkane gas is selected from one or more of methane, ethane, and propane; (5) The time of the third calcination treatment is 2-6 hours.
8. A positive electrode sheet, characterized in that: The invention comprises the lithium-supplementing positive electrode material according to any one of claims 1 to 3 or the lithium-supplementing positive electrode material prepared by the preparation method according to any one of claims 4 to 7.
9. The positive electrode sheet according to claim 8, characterized in that: The positive electrode plate comprises a current collector and a positive electrode active layer arranged on at least one side of the current collector along the thickness direction, and the positive electrode active layer is composed of the lithium supplementing positive electrode material and a binder.
10. A lithium ion battery, characterized in that: Contains the positive electrode sheet as described in claim 8 or 9.
Citation Information
Patent Citations
Preparation method of spherical lithium iron phosphate cathode material
CN102479945A
Preparation method of titanium carbide
CN109231209A
Positive electrode composite material and preparation method and application thereof
CN115312711A
Positive electrode lithium supplementing material and preparation method thereof, positive electrode plate and secondary battery
CN117525409A
Lithium supplement material for positive electrode of lithium ion battery and preparation method and application of lithium supplement material
CN117577972A